Which school-based model produces adolescent advocates for tobacco prevention in rural Maharashtra? A quasi-experimental study - Kadam, Rajashree; Bawdekar, Manasi; Chatterjee, Nilesh; Pillai, Kalpana; Gaur, Kirti (International Journal Of Community Medicine And Public Health, 2025)
Background: India’s rising non-communicable disease (NCD) burden has prompted school-based health programmes that aim to build student health and students as advocates for healthy behaviours in communities. We compared two tobacco-prevention delivery models in government schools: teacher-only tobacco-free school (TFS) training versus TFS training plus an external facilitator to examine which one encouraged more student advocates. Methods: Post-test-only quasi-experimental study conducted in four rural districts of Maharashtra. Teachers in two districts received TFS training, while two other districts received teacher training plus an external facilitator assigned for classroom delivery of health and hygiene sessions. Grade-8 students (n=1,348) from 50 schools (24 teacher-only, 26 teacher+facilitator) were surveyed. The primary outcome, “consistent commitment to advocacy,” required reporting “always” for awareness-raising with both family and community. Bivariate tests and logistic regression examined associations with knowledge, perceived TFS implementation, participation in activities, and self-efficacy (refusal, persuasion). Results: Consistent advocacy was higher in teacher-only schools [49% (293/596)] than in teacher+facilitator schools [40% (302/752)]. In adjusted analyses, being in a teacher-only school, awareness of tobacco initiatives, higher perceived fulfilment of TFS criteria, and greater refusal and persuasion self-efficacy were independently associated with consistent advocacy (all p≤0.05). Sex and knowledge scores were not significant. Conclusions: Teacher-led delivery of the TFS programme produced more consistently committed adolescent advocates. Training teachers to create health advocates/ambassadors may be a scalable approach for student-led tobacco and NCD prevention in the large-scale Ayushman Bharat government school-health program. Future research should explore mechanisms and assess impacts on actual tobacco use.